No radiographic sacroiliitis progression was observed in patients with early spondyloarthritis at 6 years: results of the Esperanza multicentric prospective cohort. Issue 2 (9th September 2020) - Fernández-Carballido, Cristina; Tornero, Carolina; Castro-Villegas, M Carmen; Galindez, Eva; García-Llorente, José Francisco; García-Vivar, María Luz; Joven-Ibáñez, Beatriz; Juanola, Xavier; Urrego-Laurín, Claudia; López-Medina, Clementina; Almodovar, Raquel; Martínez-Alberola, Nieves; et al.
Abstract : Objective: To estimate the 6-year radiographic progression of sacroiliitis in patients with early spondyloarthritis (SpA). Patients and methods: Sacroiliac joint (SIJ) radiographs (baseline and 6 years) of 94 patients with recent-onset SpA from the Esperanza cohort were scored, blindly and in a random order, by nine readers. The modified New York criteria were used to define the presence of sacroiliitis. As the gold standard for radiographic (r) sacroiliitis, the categorical opinion of at least five readers was used. Progression was defined as the shift from non-radiographic (nr) to r-sacroiliitis. Results: In the 94 SIJ radiographs (baseline and 6 years), 78/94 (83%) pairs of radiographs had not changed from baseline to 6 years. Sacroiliitis was present in 20 patients at baseline (21.3%) and in 18 (19.2%) patients at 6 years; 11 patients had sacroiliitis at both the baseline and final visits; 9 patients changed from baseline r-sacroiliitis to nr-sacroiliitis at 6 years, and 7 changed from baseline nr-sacroiliitis to r-sacroiliitis at 6 years. The mean continuous change score (range: −8 to +8) was 2.80 at baseline and 2.55 at 6 years (mean net progression of −0.25). The reliability of the readers was fair (mean inter-reader kappa of 0.375 (0.146–0.652) and mean agreement of 73.7% (58.7–90%)). Conclusion: In the early SpA Esperanza cohort, progression from nr-axSpA to r-axSpA over 6 years was not observed, although the SIJ radiographs scoring has limitations to detect low levels of radiographic progression.